IDENTIFIKASI POTENSI AKUIFER BERDASARKAN METODE GEOLISTRIK TAHANAN JENIS PADA DAERAH KRISIS AIR BERSIH DI KOTA SEMARANG - Octaviani Sarmauli; Agus Setyawan; Dwiyanto JS (Youngster Physics Journal, 2016)
Semarang city has a unique geological rock formations constituent layers in each region. The uniqueness of the identification of the presence of roundwater show that is different. Groundwater reserves in fulfilling the water requipments decreasing due to population growth, industrial growth and infrastructure development. This study aims to identify potential of aquifer to know the type of lithology layers, thickness and depth. The method used in this research is a geoelectric resistivity Schlumberger configurations with measurement points are Cangkiran, Cepoko, Ngadirgo, Gunungpati, Pakintelan, Pesantren, Tandang and Rowosari. The results suggest the potential for aquifer interpretations are based on the value of resistivity 19,6 Ωm – 92,5 Ωm with lithology as a sandstone. The aquifer grouped into the deep aquifer and the shallow aquifer. Deep aquifer has range of depth between 50-100 meters on point CA-3, CA-4, CE-1, CE-2, NG-2 and TA-1. Shallow aquifer has range of depth between 10-4 meters on point of GP, NG1, PA, PE and RO.